H3PO4/(CF3CO)2O Mediated Acylation Followed by Hurd–Mori Reaction: Synthesis of Novel 1, 2, 3‐Thiadiazol Derivatives. (24th May 2013) - Rajitha, Chittipaka; Dubey, P. K.; Sunku, Venkataiah; Veeramaneni, Venugopal Rao; Pal, Manojit
Abstract : Abstract : The synthesis of novel 1, 2, 3‐thiadiazol derivatives containing 2 H ‐benzo[ b ][1, 4]oxazin‐3(4 H )‐one moiety as one of the substituents has been reported. A combined application of H3 PO4 /(CF3 CO)2 O mediated acylation followed by Hurd–Mori reaction has been explored to synthesize these compounds. The scope and limitation of this strategy along with the reaction mechanism of the key step is discussed.